Focus on the Beauty of Body: The Mediation Role of Body Appreciation Between Perfectionism and Body-Related Shame and Body-Related Guilt - Liang, Zhang; Lingting, Shen; Ying, Cai; Xiaoyan, Liu; Yan, Zhang; Ronghua, Ying; Dan, Bi; Yanqiang, Tao (Frontiers in Psychology, 2021)
Objectives. According to traditional views, perfectionists are prone to experience shame and guilt. As a relative part of negative body image, body appreciation reflects an appreciation attitude towards physical characteristics, functionality, and health, accepting and appreciating all parts and functions of the body, predicting body-related shame and guilt. Methods. Therefore, body appreciation was examined for its potential mediating role in the relationship between two dimensions of perfectionism (e.g., healthy perfectionism and unhealthy perfectionism) and body-related shame and body-related guilt among 514 females. Results. The results highlight that body appreciation partially mediated the relationship between perfectionism and body-related shame and body-related guilt. Implications for enhancing body appreciation among females between experiencing healthy or unhealthy perfectionism and body-related shame and body-related guilt feelings are discussed. Conclusions. These findings underscore the importance of considering body appreciation in addressing perfectionism dimensions and body-related shame and body-related guilt. Research and clinical implications are also addressed.